G-POEM may be an optional treatment for refractory gastroparesis in systemic sclerosis. (2nd July 2020) - Gonzalez, Jean-Michel; Granel, Brigitte; Barthet, Marc; Vitton, Véronique
Abstract: Background: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by fibrosis involving skin and multiple internal organs. Gastrointestinal manifestations occur with a prevalence of 75–90%, and severely impact the quality of life. Among them, gastric involvement may concern 50–80% of patients with gastroparesis. GPOEM has been recently proposed as effective treatment in refractory gastroparesis, reaching 80% of short-term efficacy with very low complication rate. This procedure has never been assessed in SSc patients; thus, we describe two cases of patient who benefited from GPOEM. Patients: There were 40 and 35 years old women suffering from SSc for 10 years, whom developed gastroparesis symptoms over the last year, with GCSI score of 3.4. The diagnosis was confirmed by gastric emptying scintigraphy showing increased half emptying time and residual percentages. After failure of medical therapy associating prokinetic agents and dietary measures, they were referred after multidisciplinary discussion for GPOEM procedure. The follow-up included GCSI score calculation, adverse events, and GES at 2 months. Results: The procedures were uneventful, and the patients were discharged after 4 days and gradual refeeding. The post-operative GCSI 1 and 2.1, respectively, with both patients feeling significant clinical improvement, after a follow-up of 6 months. GES were also normalized in one patient. Despite improvement, one patient did not gain weight and had an additional jejunostomy. Conclusions: GPOEM may be an interesting therapeutic option in patient with SSc and severe gastroparesis after failure of classical treatment. This procedure could be proposed to patients after multidisciplinary discussion.